Penerapan Konsep Teori Model Betty Neuman Pada Asuhan Keperawatan Dengan Hospitalisasi Pada Anak di Rumah Sakit - Agus Khusaeni; Irna Nursanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Hospitalization is a situation where a child is required to stay and be in the hospital in a planned manner to receive care and treatment from the time he is admitted to the hospital until the child is allowed to go home again. Hospitalization is considered an event that can be stressful for children. One of the impacts of hospitalization on children is anxiety. Anxiety is a general term for hormonal changes that occur in response to threatening or frightening events or conditions, which can inhibit children's behavior, cognitive capacity, and emotional and physical health. More persistent frightening and threatening situations are more frequently experienced by children. The general aim of this case study is to implement the application of the concept of the Betty Neuman model theory to nursing care with hospitalization of children in hospitals. The research method in this case study involves the application of a nursing process approach method based on the selected nursing theory. Data collection techniques were carried out through interviews, observation, physical examination, and implementation of nursing care. The data sources used involve primary data obtained directly from patients, and secondary data originating from families, health workers, as well as documentation of other examination results to carry out nursing care. The results of nursing care by applying the Betty Neuman model theory to nursing care with hospitalization of children in hospitals are that anxiety related to hospitalization of children improves and ineffective coping related to inadequate preparation for stressors experienced by children also improves.